Antileishmanial activity of the estrogen receptor modulator raloxifene. - Juliana Q Reimão; Danilo C Miguel; Noemi N Taniwaki; Cristiana T Trinconi; Jenicer K U Yokoyama-Yasunaka; Silvia R B Uliana (Public Library of Science (PLoS), 2014)
BACKGROUND: The treatment of leishmaniasis relies mostly on parenteral drugs with potentially serious adverse effects. Additionally, parasite resistance in the treatment of leishmaniasis has been demonstrated for the majority of drugs available, making the search for more effective and less toxic drugs and treatment regimens a priority for the control of leishmaniasis. The aims of this study were to evaluate the antileishmanial activity of raloxifene in vitro and in vivo and to investigate its mechanism of action against Leishmania amazonensis. METHODOLOGY/PRINCIPAL FINDINGS: Raloxifene was shown to possess antileishmanial activity in vitro against several species with EC50 values ranging from 30.2 to 38.0 µM against promastigotes and from 8.8 to 16.2 µM against intracellular amastigotes. Raloxifene's mechanism of action was investigated through transmission electron microscopy and labeling with propidium iodide, DiSBAC2(3), rhodamine 123 and monodansylcadaverine. Microscopic examinations showed that raloxifene treated parasites displayed autophagosomes and mitochondrial damage while the plasma membrane remained continuous. Nonetheless, plasma membrane potential was rapidly altered upon raloxifene treatment with initial hyperpolarization followed by depolarization. Loss of mitochondrial membrane potential was also verified. Treatment of L. amazonensis-infected BALB/c mice with raloxifene led to significant decrease in lesion size and parasite burden. CONCLUSIONS/SIGNIFICANCE: The results of this work extend the investigation of selective estrogen receptor modulators as potential candidates for leishmaniasis treatment. The antileishmanial activity of raloxifene was demonstrated in vitro and in vivo. Raloxifene produces functional disorder on the plasma membrane of L. amazonensis promastigotes and leads to functional and morphological disruption of mitochondria, which culminate in cell death.